TRAIL and IP-10 dynamics in pregnant women post COVID-19 vaccination: associations with neutralizing antibody potency - Chen, Wei-Chun; Hu, Shu-Yu; Cheng, Chao-Min; Shen, Ching-Fen; Chuang, Hui-Yu; Ker, Chin-Ru; Sun, Der-Ji; Shen, Ching-Ju (Frontiers in Cellular and Infection Microbiology, 2024)
The aim of this study is to investigate changes in TNF-related apoptosis-inducing ligand (TRAIL) and gamma interferon-induced protein 10 (IP-10) after COVID-19 vaccination in pregnant women and to explore their association with neutralizing antibody (Nab) inhibition. The study evaluated 93 pregnant women who had previously received two (n=21), three (n=55) or four (n=17) doses of COVID-19 vaccine. Also we evaluated maternal blood samples that were collected during childbirth. The levels of TRAIL, IP-10 and Nab inhibition were measured using enzyme-linked immunosorbent assays (ELISA). Our study revealed four-dose group resulted in lower TRAIL levels when compared to the two-dose and three-dose groups (4.78 vs. 16.07 vs. 21.61 pg/ml, p = 0.014). The two-dose group had reduced IP-10 levels than the three-dose cohort (111.49 vs. 147.89 pg/ml, p=0.013), with no significant variation compared to the four-dose group. In addition, the four-dose group showed stronger Nab inhibition against specific strains (BA.2 and BA.5) than the three-dose group. A positive correlation was observed between TRAIL and IP-10 in the two-dose group, while this relationship was not found in other dose groups or between TRAIL/IP-10 and Nab inhibition. As the doses of the COVID-19 vaccine increase, the levels of TRAIL and IP-10 generally increase, only by the fourth dose,the group previously vaccinated with AZD1222 showed lower TRAIL but higher IP-10. Despite these changes, more doses of the vaccine consistently reinforced Nab inhibition, apparently without any relation to TRAIL and IP-10 levels. The variation may indicate the induction of immunological memory in vaccinated mothers, which justifies further research in the future.